2006
DOI: 10.1038/nrc1991
|View full text |Cite
|
Sign up to set email alerts
|

Polycomb silencers control cell fate, development and cancer

Abstract: Polycomb group (PcG) proteins are epigenetic gene silencers that are implicated in neoplastic development. Their oncogenic function might be associated with their well-established role in the maintenance of embryonic and adult stem cells. In this review, we discuss new insights into the possible mechanisms by which PcGs regulate cellular identity, and speculate how these functions might be relevant during tumorigenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

21
1,122
0
8

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 1,194 publications
(1,159 citation statements)
references
References 122 publications
21
1,122
0
8
Order By: Relevance
“…The lncRNA was equipped with 2 active domains, including 5′‐end that could recruit PRC2, and 3′‐end that combined with lysine specific demethylase (LSD1), RE1‐silencing transcription factor (REST) and REST co‐inhibitory protein (CoREST) 43. It was also involved with epigenetic modulation of genes, and its interaction with polycomb repressive complex 2 (PRC2) turned as a crucial process within various cellular pathways 44. Our study also demonstrated that HOTAIR acted as an oncogene for promoting retinoblastoma development (Figures 3, 4).…”
Section: Discussionmentioning
confidence: 99%
“…The lncRNA was equipped with 2 active domains, including 5′‐end that could recruit PRC2, and 3′‐end that combined with lysine specific demethylase (LSD1), RE1‐silencing transcription factor (REST) and REST co‐inhibitory protein (CoREST) 43. It was also involved with epigenetic modulation of genes, and its interaction with polycomb repressive complex 2 (PRC2) turned as a crucial process within various cellular pathways 44. Our study also demonstrated that HOTAIR acted as an oncogene for promoting retinoblastoma development (Figures 3, 4).…”
Section: Discussionmentioning
confidence: 99%
“…DNA hypermethylation in promoter regions is associated with silencing of tumor suppressor genes because of direct or indirect prevention to accessing transcription factors in the promoter region. 22 Recent studies 21,23,24 have demonstrated that CpG island hypermethylation, via silencing of key cancer-related genes, plays a major causal role in cancer, including HCC.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 In particular, Bmi1, a core molecule of polycomb repressive complex 1 (PRC1), plays an important role in the self-renewal of various stem cell systems, including hepatic stem cells. 3 Recent evidence obtained using stem cell biologybased approaches implies that a rare population of cells in tumors, termed cancer stem cells, possess extreme tumorigenic potential and share several distinctive molecular mechanisms concerning self-renewal, differentiation, and proliferation.…”
mentioning
confidence: 99%